Pengaruh Model Pembelajaran Inquiry Terbimbing terhadap Hasil Belajar Siswa Kelas X LAS pada Mata Pelajaran Dasar-Dasar Teknik Pengelasan dan Fabrikasi Logam di SMK Negeri 1 Sumbar - Muthmainnah Muthmainnah; Bulkia Rahim; Jasman Jasman; Eko Indrawan (Lembaga Yasin AlSys, 2026)
The low learning outcomes of Grade X Welding Engineering students in the Fundamentals of Welding Engineering and Metal Fabrication course at SMK Negeri 1 Sumbar were influenced by a learning process that remained dominated by the lecture method, resulting in students being less active and motivated to participate in learning. This study aimed to describe the implementation of the guided inquiry learning model and analyze its effect on students’ learning outcomes. The study employed an experimental method with a one-group pretest–posttest design. The research sample included all 35 Grade X LAS students at SMK Negeri 1 Sumbar. Data were collected using a learning achievement test that had been assessed for validity, reliability, difficulty level, and discriminating power. The data were analyzed through normality and homogeneity tests, followed by hypothesis testing using a paired-samples t-test. The results showed that the mean posttest score was 83.86, which was higher than the mean pretest score of 61.20. The hypothesis test yielded a significance value of 0.000 < 0.05; therefore, H₀ was rejected and Hₐ was accepted at a significance level of α = 0.05. These findings indicated a significant difference in learning outcomes before and after the implementation of the guided inquiry learning model. Thus, the guided inquiry learning model had a significant effect on the learning outcomes of Grade X LAS students in the Fundamentals of Welding Engineering and Metal Fabrication course at SMK Negeri 1 Sumbar. The implementation of this model can serve as an alternative learning approach that promotes student activeness and improves learning achievement in vocational education.